DIFFERENCES BETWEEN ARBITRATION AND STATE COURTS (Scientific journal of the Fergana State University, 2024)
What are the differences between arbitration courts, which are now playing an increasingly important role in alternative dispute resolution, and state courts, which are significantly less burdened by disputes, and what are their advantages and disadvantages? In this article, covering answers to such questions, the general and main differences between the concept of the Arbitration Court and the state courts have been shown, and their advantages and disadvantages have been studied and discussed in detail.